Spectroscopic, electronic and computational properties of a mixed tetrachalcogenafulvalene and its charge transfer complex. Issue 5 (18th January 2018) - Walwyn, Robert J.; Chan, Bun; Usov, Pavel M.; Solomon, Marcello B.; Duyker, Samuel G.; Koo, Jin Young; Kawano, Masaki; Turner, Peter; Kepert, Cameron J.; D'Alessandro, Deanna M.
Abstract : The unexplored electron donor molecule triselenathiafulvalene (TSTF) and its corresponding charge transfer complex with the well-known electron acceptor TCNQ exhibit rich electronic, optical and semiconducting properties. Abstract : This paper reports additional properties of the electron donor molecule triselenathiafulvalene (TSTF) and its synthesis via a new route involving the precursor tetracarbomethoxytriselenathiafulvalene (TCMTSTF). The structural, electronic and computational properties of TSTF are fully profiled, and discussed in the context of the closely related archetypal electron donor molecule tetrathiafulvalene (TTF). TSTF was also incorporated into a charge transfer (CT) complex with the well-known electron acceptor 7, 7, 8, 8-tetracyanoquinodimethane (TCNQ), to generate TSTF–TCNQ. In order to establish its position in the greater TXF–TCNQ series (where TXF = a tetrachalcogenafulvalene), spectral, electrochemical, magnetic, conductivity and computational studies were performed on TSTF and TSTF–TCNQ to extend what is known about the highly interesting and useful new donor molecule.